Electroacupuncture Reduces Anxiety Associated With Inflammatory Bowel Disease By Acting on Cannabinoid CB1 Receptors in the Ventral Hippocampus in Mice - Hu, Xue-Fei; Zhang, Hong; Yu, Ling-Ling; Ge, Wen-Qiang; Zhan-mu, Ou-Yang; Li, Yan-Zhen; Chen, Chao; Hou, Teng-Fei; Xiang, Hong-Chun; Li, Yuan-Heng; Su, Yang-Shuai; Jing, Xiang-Hong; et al. (Frontiers in Pharmacology, 2022)
The therapeutic effect of electroacupuncture (EA) on the comorbidity of visceral pain and anxiety in patients with inflammatory bowel disease (IBD) is well known. It has been known that the ventral hippocampus (vHPC) and the cannabinoid type 1 receptors (CB1R) are involved in regulating anxiety and pain. Therefore, in this study, we determined whether EA reduces visceral pain and IBD-induced anxiety via CB1R in the vHPC. We found that EA alleviated visceral hyperalgesia and anxiety in TNBS-treated IBD mice. EA reversed over-expression of CB1R in IBD mice and decreased the percentage of CB1R-expressed GABAergic neurons in the vHPC. Ablating CB1R of GABAergic neurons in the vHPC alleviated anxiety in TNBS-treated mice and mimicked the anxiolytic effect of EA. While ablating CB1R in glutamatergic neurons in the vHPC induced severe anxiety in wild type mice and inhibited the anxiolytic effect of EA. However, ablating CB1R in either GABAergic or glutamatergic neurons in the vHPC did not alter visceral pain. In conclusion, we found CB1R in both GABAergic neurons and glutamatergic neurons are involved in the inhibitory effect of EA on anxiety but not visceral pain in IBD mice. EA may exert anxiolytic effect via downregulating CB1R in GABAergic neurons and activating CB1R in glutamatergic neurons in the vHPC, thus reducing the release of glutamate and inhibiting the anxiety circuit related to vHPC. Thus, our study provides new information about the cellular and molecular mechanisms of the therapeutic effect of EA on anxiety induced by IBD.